Natural Gas Markets in the U.K. : Competition, Industry Structure, and Market Power of the Incumbent - Juris, Andrej (World Bank, Washington, DC, 2012)
The deregulation of the U.K. natural gas industry has facilitated new entry and competition in almost all segments of the industry except pipeline transportation. The new regulatory framework, developed largely by the Office of Gas Regulation (Ofgas), has allowed market forces to stimulate a variety of specialized services and market transactions to meet customer needs. But the entire process has been difficult because of a flaw in the initial industry structure: the government privatized British Gas as a vertically integrated company. The U. K. experience shows that leaving gas supply integrated with pipeline transportation and tying up gas in long-term contracts impede competition. This Note reviews the U.K. reform and the development of new spot, on-system, and "Flexibility Mechanism" markets.